Komparasi Metodologis Konsep Sunnah Menurut Fazlur Rahman dan Muhammad Syahrur (Perspektif Hukum Islam) - Vita Fitria (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2011)
Two figures of contemporary moslem scholar, Fazlur Rahman and Muhammad Syahrur, have unique, dynamic conception and comprehension toward Sunnah and Hadits different from other scholars and moslems` comprehension in general. Both Rahman and Syahrur, emphasize more on methodological criticism on Sunnah and Hadits instead of criticism on matan and sanad. According to Rahman, the existence of hadits are historically improvable. Basically, the concept of sunnah have been existing since Islam born. It was merely guidance and protective in its nature. It embraced interpretations fit to situation and condition at the time, often considered as "living Sunnah" . Rahman`s criticism on recent condition is a comprehension toward hadits which tends to be stiff, unchangeable and even moresacred than Al-Qur`an itself, whereas Syahrur`s is method to apply laws in ummul kitab in simple way by breaking no rules settled by Allah. In Syahrur`s, it places custom laws as the determiner for problems still uncovered in law by noticing objective standard covering the context of space and time.